2012
DOI: 10.1016/j.jcrs.2011.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Visual quality assessment in patients with orange-tinted blue light–filtering and clear ultraviolet light–filtering intraocular lenses

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…A recent study with similar design and results had an even smaller sample size of 22 patients. 43 For macular evaluation, besides OCT and clinical evaluation, fundus autofluorescence (FAF) may be used to provide additional information not obtainable with other imaging techniques. It is known that FAF changes in ARMD do not correlate with clinically visible alterations, and it was assumed that abnormal FAF reflects more widespread macular changes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with similar design and results had an even smaller sample size of 22 patients. 43 For macular evaluation, besides OCT and clinical evaluation, fundus autofluorescence (FAF) may be used to provide additional information not obtainable with other imaging techniques. It is known that FAF changes in ARMD do not correlate with clinically visible alterations, and it was assumed that abnormal FAF reflects more widespread macular changes.…”
Section: Discussionmentioning
confidence: 99%
“…4 The clear, ultraviolet (UV)-blocking and the yellow-colored IOLs currently available show similar properties in terms of visual function with the exception of vision in mesopic or scotopic light conditions. [5][6][7][8][9] Glare reduction is an additional advantage of yellow-colored IOL, although concerns have been raised that the blue lightblocking effects of such a lens might disturb normal circadian rhythms 10,11 because intrinsically photosensitive retinal ganglion cells mediate melatonin secretion by photoreception of blue light. [12][13][14] On the contrary, clear IOLs do not block visible light transmission and thus offer no protection to the retina from the potentially damaging effects of bright light, [15][16][17][18][19][20] although the protective effect of a blue lightblocking IOL is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, Schmack et al 37 reported similar results after implantation of an orange-tinted IOL and a clear UV lightfiltering IOL. They report comparable postoperative visual function except for color perception, which was slightly better in eyes with a clear IOL.…”
Section: Discussionmentioning
confidence: 84%